A statistical analysis of the relationship between working capital management and profitability: Evidence from selected manufacturing companies of Bangladesh (IIUC Business Review, 2021)
The aim of this study is to measure the relationship between working capital management and profitability. The research is based on secondary data derived from annual reports of companies listed on Bangladeshi stock exchanges. The sample spans nine years, from 2011 to 2019, and includes 52 manufacturing enterprises in Bangladesh, including 20 pharmaceutical companies and 32 textile companies. The cash conversion cycle is significantly positively associated with profitability, the average collection period is significantly negatively associated with profitability, and the inventory conversion period is also significantly negatively associated with profitability, but the average payable period is not significantly associated with profitability. This research adds to the literature by focusing on working capital management and profitability, particularly in the textile and pharmaceutical industries. There have been a few research on this topic, however they are limited in sample size and time period. This research looks at all active businesses in these two industries. As a result, policymakers in these disciplines may utilize these findings to make decisions.IIUC Business Review Vol. 10, Dec. 2021 pp. 101-114